2021
DOI: 10.3390/toxins13030177
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Renal Transcriptomics after Subchronic Exposure to Ochratoxin A in Fisher Rats

Abstract: The mycotoxin ochratoxin A (OTA) is a potent nephrocarcinogen, mainly in male rats. The aim of this study was to determine the time course of gene expression (GeneChip® Rat Gene 2.0 ST Array, Affymetrix) in kidney samples from male and female F344 rats, treated daily (p.o) with 0.50 mg/kg b.w. (body weight) of OTA for 7 or 21 days, and evaluate if there were differences between both sexes. After OTA treatment, there was an evolution of gene expression in the kidney over time, with more differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 43 publications
5
21
2
Order By: Relevance
“…pathways (Ayed-Boussema et al 2012;Doricakova and Vrzal, 2015), hepatocyte nuclear factor 4 alpha (Hnf4α) (Pastor et al, 2018b;Marin-Kuan et al, 2006) and nuclear factor-erytroid 2-related factor (Nrf2) (Limonciel and Jennings, 2014). In addition, as it was described in Pastor et al, 2018b, several of these signaling pathways showed a clear sex-dependent response.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 4 more Smart Citations
“…pathways (Ayed-Boussema et al 2012;Doricakova and Vrzal, 2015), hepatocyte nuclear factor 4 alpha (Hnf4α) (Pastor et al, 2018b;Marin-Kuan et al, 2006) and nuclear factor-erytroid 2-related factor (Nrf2) (Limonciel and Jennings, 2014). In addition, as it was described in Pastor et al, 2018b, several of these signaling pathways showed a clear sex-dependent response.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…pathways (Ayed-Boussema et al 2012;Doricakova and Vrzal, 2015), hepatocyte nuclear factor 4 alpha (Hnf4α) (Pastor et al, 2018b;Marin-Kuan et al, 2006) and nuclear factor-erytroid 2-related factor (Nrf2) (Limonciel and Jennings, 2014). In addition, as it was described in Pastor et al, 2018b, several of these signaling pathways showed a clear sex-dependent response. Finally, these pathways could be relevant in others functions such as cell cycle progression or apoptosis, such as Ahr that has been proposed to be related with to some mechanisms of hepatocarcinogenesis (Souza et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 3 more Smart Citations